The molecular mechanisms of IUGR programmed adulthood cardiovascular disease - Wu, Ting; Zhang, Wen; Wang, Yangong; Luo, Hong; Li, Yifei (Frontiers in Cell and Developmental Biology, 2025)
Intrauterine growth restriction (IUGR) is secondary to several maternal and fetal adverse conditions. Recently, there is a convincing association between the onset of IUGR and adulthood programmed complications. Among them, the disorders in the cardiovascular system have been revealed by a series of researches. Currently, the prevalence of IUGR is considered to be related to programmed hypertension, coronary artery lesions, pulmonary hypertension, metabolic dysfunction, and even heart failure. According to the emerging knowledge in this field, the experiences of IUGR would induce prolonged inflammation, oxidative injuries, aberrant metabolites and epigenetic regulation, which resulted in endothelial, smooth muscle cells and cardiomyocytes damages. In this review, we summarized the evidences and progress in establishing the association between IUGR and programmed cardiovascular diseases and involved molecular mechanisms. Furthermore, we also discussed the potential efficient therapeutic strategies. This comprehensive review demonstrated that IUGR manifested long-term consequences persisting into adulthood through multifaceted molecular pathways, notably oxidative stress mechanisms, mitochondrial dysfunction, and epigenetic alterations. These findings underscored the critical importance of implementing early preventive interventions and developing personalized therapeutic approaches in future clinical practice.